Factors Influencing the Lack of Information on Dyslexia among Future English Language Teachers (A Case of Four Universities in Georgia) - Nino Zaalishvili (European Scientific Journal, ESJ, 2023)
The main purpose of the study is to investigate factors that influence the lack of information on dyslexia among future English language teachers. In particular, the factors under investigation in this study are a low level of knowledge about dyslexia; not enough readiness to teach students with dyslexia; universities not providing enough information about dyslexia; there is a lack of information about shadow education and there exist internal and external factors like: there are not conducting training regularly about dyslexia among students, and students do not attend the lectures regularly.A quantitative research approach based on a questionnaire was employed. 120 students from the program of English Philology were asked to complete the survey from four universities in Tbilisi, Georgia. The research was conducted in October 2023. A quantitative method was used to examine future English language teachers’ level of knowledge about dyslexia.The findings indicated that insufficient information about dyslexia negatively impacts the future English language teachers’ readiness to teach students with dyslexia. Another factor is students’ motivation to attend the lectures, if they are not attending the lectures regularly, there is less chance that they would attend the training about dyslexia.It is suggested to raise awareness and provide information to future English language teachers about dyslexia, but at first, their motivation should be increased. University programs should have special education subjects and should persuade future teachers that special education is beneficial for the whole class, to be created a healthy classroom climate.